Coexistent Cerebral Cavernous Malformation and Developmental Venous Anomaly: Does an Aggressive Natural History Always Call for Surgical Intervention? - Das, Kuntal Kanti (Asian J Neurosurg, 2019)
Coexistence of cerebral cavernous malformations (CMs) and developmental venous anomaly (DVA) represents the most common form of mixed intracranial vascular malformations. Existing literature supports not only a possible causative role of DVA for de novo CMs but also a potentially detrimental effect on an associated CM, increasing the chances of hemorrhagic complications and growth in the latter. A 52-year-old gentleman presented to us with a 17-year long history of simple motor seizures on the left faciobrachial region. On magnetic resonance imaging (MRI) of the head, a 1.5 cm × 1.5 cm CM without any evidence of recent hemorrhage was identified in the left high frontal premotor area. There was a linear enhancement in the adjoining superior frontal sulcus on contrast MRI. On intra-arterial angiogram, this hyperintensity was confirmed to be a venous channel draining into the superior sagittal sinus. Thus, a diagnosis of cavernoma associated with a DVA was made. The patient was advised conservative treatment and he was doing well at follow-up. Unless diligently looked for, DVA associated with CM may be easily missed. The coexistence has pathophysiological and management implications. Despite the reported aggressive natural history, there is a scope for conservative treatment for these complex vascular malformations.